Compounds Combining Aminoadamantane and Monoterpene Moieties: Cytotoxicity and Mutagenic Effects - Suslov, Evgeniy V; Ponomarev, Konstantin Yu; Rogachev, Artem D; Pokrovsky, Michail A; Pokrovsky, Andrey G; Pykhtina, Maria B; Beklemishev, Anatoly B; Korchagina, Dina V; Volcho, Konstantin P; Salakhutdinov, Nariman F (Medicinal chemistry (Shp-sariqah, United Arab Emirates), 2015)
A series of secondary amines combining monoterpenoid and aminoadamantane moieties have been synthesized. Their cytotoxic activity against human cancer cells CEM-13, MT-4, and U-937 has been studied for the first time. Most of the obtained compounds exhibited a significant cytotoxic activity with the median cytotoxic dose (CTD50) ranging from 6 to 84 µM. The most promising results were obtained for compound 2b which was synthesized from 1-aminoadamantane and (-)-myrtenal and revealed a high activity against all tumor lines used (CTD50 = 12 ÷ 21 µM) along with low toxicity with respect to MDCK cells (CTD50 = 1500 µM). The synthesized amines do not exert the genotoxic effect on cells of the biosensor strain based on recombinant E. coli cells bearing the pRAC-gfp plasmid.